General and substantive theories of the media and audiences - Vladimir Argudo Palomeque (Technium Social Sciences Journal, 2020)
The use of new technologies as instruments of rapprochement between the public and the radio gives us a meaning of the power that the media have to announce what happens daily in society, applying techniques that allow them to be in the place where the events take place. facts and transmit them as they are, from the journalist’s perception that allows him to get closer to the truth and why get closer to the truth, because the journalist must remember that one of the rules that govern this activity is the fact of asking and asking questions until to have the information that is needed and not to believe any version that the source expresses, and especially because doubt is the essence of journalism. Public participation in the media is a phenomenon that has emerged and has been promoted in recent years in Cuenca. Now not only with the use of the conventional telephone but with the application of technology such as: Internet, cell phone messages, emails and chats that have made the newscasts the most popular genre by audiences. This construction motivates the investigation of theories that support this position. In this context, we currently live in a technological culture that advances day by day and that marks in a matter of months a rapid obsolescence of much knowledge and the emergence of others. The impact of this culture is immense since it produces continuous transformations in economic, social and cultural globalization, and affects practically all aspects of personal life: work, commerce, bureaucratic management, leisure and education. For these reasons, technology urgently requires learning to live with it and authorize its undoubted benefits.